The Protective Effect of Propofol Against Ischemia-Reperfusion Injury in the Interlobar Arteries: Reduction of Abnormal Cx43 Expression as a Possible Mechanism - Yue-Chen Chang; Wen-Jing Xue; Wei Ji; Yang Wang; Yan-Ping Wang; Wen-Yan Shi; Li-Ya Shan; Liang Zhang; Chao-Yang Tan; Ke-Tao Ma; Li Li; Jun-Qiang Si (Karger Publishers, 2018)
Background/Aims: This experimental study aims to observe whether the protective effect of propofol against renal ischemia-reperfusion injury (IRI) in the rat interlobar artery occurs through altered expression of the gap junction protein connexin 43 (Cx43). Methods: This study randomly divided male Sprague Dawley (SD) rats into an untreated control group, a sham-operated control group (sham group), an ischemia-reperfusion group (IR group), a propofol group (propofol+IR group) and a fat emulsion group (Intralipid group). The ischemia/reperfusion model was prepared through resection of the right kidney and noninvasive arterial occlusion of the left kidney. Forty-five minutes after renal ischemia-reperfusion, an automatic biochemical analyzer was employed to measure blood urea nitrogen (BUN) and serum creatinine (SCr); changes in renal tissue pathology were observed using hematoxylin and eosin (HE) staining, and the vasomotor activity of the interlobar artery was detected using a pressure mechanogram technique. The protein expression of Cx43 in renal artery cross-sections was determined through western blotting. Results: The experimental study confirmed that the BUN and SCr of rats markedly increased after ischemia-reperfusion injury; additionally, we observed some coagulation necrosis and shedding of cells, some solidification of nuclear chromatin, degeneration of cytoplasmic vacuoles, high renal interstitial vascular congestion and obvious inflammatory cell infiltration, characterized by focal hemorrhages. Furthermore, the contraction activity of the renal interlobar artery greatly decreased, and the tension of the arteries in the renal lobe increased remarkably. After the gap junction blocking agents 2-APB and Gap27 were applied, the systolic velocity of blood vessels and the vascular contraction rate both decreased. In addition, the expression of Cx43 in kidney tissues increased markedly. The damage was more severe after 24 h of ischemic reperfusion than after only 4 h. However, after pretreatment with propofol, regardless of whether ischemia-reperfusion was applied for 4 h or 24 h, the previously increased expression of Cx43 decreased obviously, and all forms of renal damage were reversed. Conclusion: Our research suggests new ways for propofol to relieve ischemia-reperfusion injury by decreasing the abnormal expression of the gap junction protein Cx43. This study reveals a novel mechanism for the action of propofol against IRI, and we hope this finding will lead to new treatments for IRI.